Quantification of ferroptosis pathway status revealed heterogeneity in breast cancer patients with distinct immune microenvironment - Li, Yuying; Li, Tianfu; Zhai, Duanyang; Xie, Chuanbo; Kuang, Xiaying; Lin, Ying; Shao, Nan (Frontiers in Oncology, 2022)
Clinical significance and biological functions of the ferroptosis pathway were addressed in all aspect of cancer regarding multi-omics level, however, the overall status of ferroptosis pathway alteration was hard to evaluate. The aim of this study is to comprehensively analyze the putative biological, pathological and clinical functions of the ferroptosis pathway in breast cancer on a pathway level. By adopting the bioinformatic algorithm “pathifier”, we quantified five programmed cell death (PCD) pathways (KO04210 Apoptosis; KO04216 Ferroptosis; KO04217 Necroptosis; GO:0070269 Pyroptosis; GO:0048102 Autophagic cell death) in breast cancer patients, we featured the clinical characteristics and prognostic value of each pathway in breast cancer, found significantly activated PCD in cancer patients, among which ferroptosis was demonstrated significant correlation with the prognosis of breast cancer. Correlation analysis between PCD pathways identified intra-tumor heterogeneity of breast cancer. Therefore, clustering of patients based on the status of PCD pathways was done. Comparisons between subgroups highlighted specifically activated ferroptosis in cluster 2 patients, which showed distinct status of tumor immunity and microenvironment from other clusters, indicating putative correlations with ferroptosis. NDUFA13 was identified and selected as a putative biomarker for cluster 2 patients. Experimental validations were executed on cellular level and NDUFA13 showed an important role in regulating ferroptosis activation and can work as a biomarker for ferroptosis pathway status. In conclusion, the status of ferroptosis pathway significantly correlated with the clinical outcomes and intra-tumor heterogeneity of breast cancer and NDUFA13 expression was identified as a positive biomarker for ferroptosis pathway activation in breast cancer patients.